2007
DOI: 10.1007/s10865-007-9142-3
|View full text |Cite
|
Sign up to set email alerts
|

The association of benefit finding to psychosocial and health behavior adaptation among HIV+ men and women

Abstract: Psychological and behavioral adaptation to HIV is integral to long-term survival. Although most research on coping with HIV has focused on factors associated with poor adaptation, recent research has expanded to include positive concomitants of adaptation, such as benefit finding. This study examined the occurrence of benefit finding among HIV+ men and women and evaluated the potential relevance of benefit finding to positive health behavior and psychosocial adaptation. HIV+ participants (N = 221) recruited du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 71 publications
4
54
0
Order By: Relevance
“…First, because participants completed all measures at one time point with one assessment approach, we are limited in our ability to draw causal conclusions. In particular, whereas we conceptualized stress-related growth as a coping resource of gay and bisexual men (see Golub et al, 2010, for a similar conceptualization of stress-related growth among transgender individuals; see also Littlewood et al, 2008; Milam, 2006), we acknowledge that stress-related growth can also be viewed as a positive outcome that results from life stressors (Helgeson et al, 2006). In other words, it is possible that gay and bisexual men who were more well-adjusted (e.g., experienced fewer emotion regulation difficulties and mental health problems) were more likely to experience stress-related growth in relation to their sexual orientation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, because participants completed all measures at one time point with one assessment approach, we are limited in our ability to draw causal conclusions. In particular, whereas we conceptualized stress-related growth as a coping resource of gay and bisexual men (see Golub et al, 2010, for a similar conceptualization of stress-related growth among transgender individuals; see also Littlewood et al, 2008; Milam, 2006), we acknowledge that stress-related growth can also be viewed as a positive outcome that results from life stressors (Helgeson et al, 2006). In other words, it is possible that gay and bisexual men who were more well-adjusted (e.g., experienced fewer emotion regulation difficulties and mental health problems) were more likely to experience stress-related growth in relation to their sexual orientation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the perception of personal growth as a result of one’s illness was associated with fewer depressive symptoms, lower substance use, and greater physical activity among HIV-positive individuals (Littlewood, Carey, Vanable, & Blair, 2008; Milam, 2006). It is unclear, however, whether these findings would generalize to the context of managing stigma-related stressors, which can pose unique, ongoing coping demands for individuals from socially-disadvantaged groups.…”
mentioning
confidence: 99%
“…For example, one study found that people who found benefit or meaning in a recent trauma experienced less psychological distress than did people who did not find such benefit, controlling for pre-trauma distress (Davis et al, 1998). Similarly, a study of HIV' men and women found that benefit-finding was linked to higher levels of physical activity and less depression (Littlewood, Vanable, Carey, & Blair, 2008). Another study found that benefit-finding in women with breast cancer predicted greater well-being after the diagnosis for up to 5Á8 years (Carver & Antoni,152 K. Sweeny and A.G. Cavanaugh 2004).…”
Section: Benefit-findingmentioning
confidence: 99%
“…Many of the affective consequences of uncertainty navigation have already been discussed. For example, expectation management can reduce the likelihood of experiencing disappointment and other negative emotions (Shepperd & McNulty, 2002;Sweeny & Shepperd, in press) and benefit-finding can increase well-being (Carver & Antoni, 2004;Sprangers & Schwartz, 1999) and decrease distress and depression (Davis et al, 1998;Littlewood et al, 2008). Though speculative, one hypothesis deriving from the model is that people who find reasons to believe that health feedback is unreliable, biased or otherwise invalid are also less likely to experience distress in response to bad news.…”
Section: Health Psychology Review 153mentioning
confidence: 99%
“…Diseases which are incurable, have visible symptoms, and for which the infected individuals are marked as responsible for spreading it, are more potential for stigmatisation. AIDS f its perfectly into this category and carries the signif icant stigma (Brimlow , 2014;Littlewood , 2008;Vanable , 2006). Stigma is one of the factors that adversely influence population health (Hatzenbuehler , 2009).…”
Section: Introductionmentioning
confidence: 99%